A new species of Tanytarsus van der Wulp, 1874 (Diptera: Chironomidae) and the first Japanese record of Tanytarsus ovatus Johannsen, 1932 with DNA barcodes - Kodama, Atsuya; Kawai, Koichiro; Saito, Hidetoshi (Zootaxa, 2018)
A new species of the genus Tanytarsus van der Wulp, 1874 was described and illustrated based on an adult male. Tanytarsus trichovalis sp. nov. belongs to the eminulus species group, and is closely related to T. tamaundecimus Sasa, 1980, T. okuboi Sasa, 1986, and T. tonebeceus Sasa & Tanaka, 2000. However, the species is distinguished from these species by the morphology of the hypopygium. We also present the first record of T. ovatus Johannsen, 1932 in Japan. In addition, DNA barcoding of 5 species including T. trichovalis sp. nov., T. ovatus, and other morphologically related species was undertaken. A new key of the eleven Japanese eminulus species group was compiled.